Loreal as an Employer of Choice for a Male Target Group - Sádlová, Barbora (2018)
The research maps out the perception of L'Oréal as an employer by the male VŠE students and fresh graduates. Based on the focus group with the male target group, L'Oréal is on one hand seen as a leader in its industry, with a lot of flexibility and desire to hire, on the other, as a female-oriented company that neglects its employees. The research also investigates on the tools which could help L'Oréal attract the male target group to join the company. Based on the comparison from focus group with the male target group and focus group with L'Oréal's employees, the author identifies that the company should adapt more complex and professional recruiting process that would illustrate the aspect of exclusivity. The company should also offer the male target group better incentives in form of more competitive salary and better benefits in order to overcome the L'Oréal's perception of a female company.